Candida africanain recurrent vulvovaginal candidiasis (RVVC) patients: frequency and phenotypic and genotypic characteristics. Issue 11 (November 2018) - Naeimi, Behrouz; Mirhendi, Hossein; Khamisipour, Gholamreza; Sadeghzadeh, Farzaneh; Ahmadi, Bahram
Abstract : Purpose. : Up to 75 % of all women develop vulvovaginal candidiasis (VVC), with symptoms such as vulvar erythema, pruritus and abnormal vaginal discharge. Despite the global distribution of Candida africana, its role in recurrent vulvovaginal candidiasis (RVVC) is still unclear and requires further investigation. Here, we report on the frequency of C. africana among clinical isolates from patients with RVVC in Bushehr in southern Iran. Methodology. : Isolated Candida strains were identified by ITS‐PCR‐RFLP. Hyphal wall protein 1 ( HWP1 ) was amplified to differentiate C. africana and the resulting sequences were subjected to phylogenetic analyses with a view to identifying similarities and differences in nucleotides. Results. : Ten out of 119 strains originally identified as C. albicans turned out to be C. africana . Pairwise nucleotide alignment of HWP1 DNA sequences showed 100 % similarity between C. africana strains. Inter‐species variation between Iranian C. africana HWP1 sequences and the only three available C. africana type sequences in GenBank revealed 99.7‐100 % nucleotide similarity. Phylogenetic analysis of the HWP1 DNA sequences of 10 Iranian C. africana isolates, the 3 C. africana sequences available in GenBank and 2 representative Iranian C. albicans sequences revealed that all 11 Iranian C. africana strains formed a well‐supported cluster separated from the remaining C. africana . Conclusion. : In our sample, C. africana was only isolated from 7.8 % of the patients with RVVC. While size polymorphisms in HPW1 genes allowed us to differentiate C. africana from C. albicans, no evidence of sequence variation within the Iranian C. africana isolates was observed.